IMPLEMENTASI METODE ELECTRE UNTUK MENENTUKAN KELAYAKAN PEMBERIAN KREDIT SEPEDA MOTOR PADA PERUSAHAAN LEASING - Dinil Lativa; Poningsih Poningsih; Jalaluddin Jalaluddin (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Leasing companies are financing equipment or capital goods that are used for the production process of a company, both directly and indirectly. Financing through leasing is a very simple financing in the procedures and implementation and therefore leasing that is used as an alternative payment seems more attractive. As an alternative source of capital financing for companies, especially in the credit analyst section. In credit-worthy consumer decision-making activities, a computer-based system model that can provide data analysis, calculation of criteria for credit applicants, and help processing data into information to make decisions from the semi-structured problem is needed. A decision system (DSS) is the right choice to help select credit applicants. The system is designed with the Elimination and Choice Translating Reality (ELECTRE) method which is one of the multi criteria calculation methods based on the outrangking concept map by using paired comparisons of other alternatives based on each criterion. The data used in this paper are in the form of alternative data samples, criteria data, criteria weight, and suitability rating for each alternative to the criteria.Keywords: ELECTRE, Credit Analyst ,Kredit, Leasing